PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA PT. PEGADAIAN (PERSERO) CABANG SELONG - Didin Hadi Saputra (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2015)
The Services at the pawning house of PT. Pegadaian ( Ltd ) of Selong Branch Office are mostlypawning service. Pawning service is one of the main services provided by PT. Pegadaian (Ltd) ofSelong Branch Office. This study aims at observing five variables to identify customers’ satisfaction.Those five variables are reliability (X1), responsiveness (X2), assurance (X3), emphaty (X4), andtangibles (X5). This is an associative study using quetionnaires for data collection. Data is thenanalyzed the multiple linear regression analysis. The study reveals that the variables of reliability(X1), responsiveness (X2), assurance (X3), emphaty (X4), and tangibles (X5) both simultaneously andseparately have a significant and positive effect towards customers’ satisfaction. This, thehypothesis of the study is accepted. Accordingly, PT. Pegadaian (Ltd) of Selong Branch Office is tomaintain the implementation of the five variables. Also, it is also suggested that PT. Pegadaian (Ltd)of Selong Branch Office improve the tangible facilities such as suggestion box, AC, trash cans, andthe space layout.Keywords : services, customer’ satisfaction, service quality, multiple linear regression.